Characterization of 4-Hydroxyphenylacetate 3-Hydroxylase (HpaB) of Escherichia coli as a Reduced Flavin Adenine Dinucleotide-Utilizing Monooxygenase - Xun, Luying (American Society for Microbiology, 2000)
4-Hydroxyphenylacetate 3-hydroxylase (HpaB and HpaC) of Escherichia coli W has been reported as a two-component flavin adenine dinucleotide (FAD)-dependent monooxygenase that attacks a broad spectrum of phenolic compounds. However, the function of each component in catalysis is unclear. The large component (HpaB) was demonstrated here to be a reduced FAD (FADH(2))-utilizing monooxygenase. When an E. coli flavin reductase (Fre) having no apparent homology with HpaC was used to generate FADH(2) in vitro, HpaB was able to use FADH(2) and O(2) for the oxidation of 4-hydroxyphenylacetate. HpaB also used chemically produced FADH(2) for 4-hydroxyphenylacetate oxidation, further demonstrating that HpaB is an FADH(2)-utilizing monooxygenase. FADH(2) generated by Fre was rapidly oxidized by O(2) to form H(2)O(2) in the absence of HpaB. When HpaB was included in the reaction mixture without 4-hydroxyphenylacetate, HpaB bound FADH(2) and transitorily protected it from rapid autoxidation by O(2). When 4-hydroxyphenylacetate was also present, HpaB effectively competed with O(2) for FADH(2) utilization, leading to 4-hydroxyphenylacetate oxidation. With sufficient amounts of HpaB in the reaction mixture, FADH(2) produced by Fre was mainly used by HpaB for the oxidation of 4-hydroxyphenylacetate. At low HpaB concentrations, most FADH(2) was autoxidized by O(2), causing uncoupling. However, the coupling of the two enzymes' activities was increased by lowering FAD concentrations in the reaction mixture. A database search revealed that HpaB had sequence similarities to several proteins and gene products involved in biosynthesis and biodegradation in both bacteria and archaea. This is the first report of an FADH(2)-utilizing monooxygenase that uses FADH(2) as a substrate rather than as a cofactor.